Yield performance with heritability measurements of half sib families obtained from maize variety Azam - ur-Rahman, Nazir Ahmad, Faizan Mahmood, Hidayat-; Haq, Fahim-ul-; Quaid Hussain, Samrin Gul,; Khalid, Ammara; Iqbal, Touheed; Rozi, Sidra (Journal of Experimental Sciences)
This study evaluated the performance of 64 half sib families (HSF) derived from “Azam” variety of maize using partially balanced lattice square design with two replications. Data were recorded on grain yield and other agronomic traits. Observations showed difference in half-sib families for studied traits. Among the 64 half-sib families, minimum days to 50% tasseling (51 days) were observed for HS-49 while maximum (57 days) for HS-63. Minimum days to 50% silking (56 days) were counted for HS-6 while maximum (63 days) for HS-23. Minimum days to 50% anthesis (55 days) were counted for HS-1 and HS-6 while maximum (62 days) for HS-23. Similarly, minimum ASI (-2 days) were observed in HS-1, HS-15, HS-16, HS-28 and HS-63 while maximum (2 days) in HS-48. Minimum (60 cm) ear height was recorded for HS-11 and maximum (93.5 cm) for HS-28. Minimum fresh ear weight (1.3 kg) was weighted for HS-17 while maximum (3.2 kg) for HS-21. Grain moisture was recorded minimum (19.35 %) for HS-19 and maximum (31.25%) for HS-2. HS-42 showed minimum (28 g) 100 kernel weight while HS-5 showed maximum (47 g). Grain yield was minimum (2323 kg ha-1) for HS-17 and maximum (5742 kg ha-1) for HS-21. Maximum heritability estimate (0.92) was recorded for fresh ear weight, while minimum (0.41) was observed for ear height.